Alginate-polyvinyl alcohol based interpenetrating polymer network for prolonged drug therapy, Optimization and in-vitro characterization. (15th June 2017) - Anwar, Hina; Ahmad, Mahmood; Minhas, Muhammad Usman; Rehmani, Sahrish
Highlights: Sodium Alginate-PVA hydrogels with different polymeric compositions prepared according to 3 2 full factorial design were used. PH independent characteristics was observed for IPN hydrogels obtained through free radical polymerization. Out of four dependent variables the two i.e. q18h and R 18h were directly proportional to polymer and inversely proportional to the concentration of AMPS while t80% and DEE (%) were increased significantly on increasing either contents of Na-alginate or AMPS. Optimized formulation (FSP-10) showed 56.34% of tramadol release at 18th hour, t80% (h) of 30 h, and DEE of 23.99%, thereby confirming prolonged drug release characteristics. Abstract: A new natural and synthetic polymeric blend to form interpenetrating polymer network (IPN) hydrogels was synthesized utilizing sodium alginate and PVA as polymers by free radical polymerization employing 2-Acylamido-2-methylpropane-sulfonic acid as monomer (AMPS) and tramadol HCl as model drug through 3 2 level full factorial design to evaluate the impact of selected independent factors i.e. polymer (sodium alginate) and monomer (AMPS) contents on swelling index at 18th hour, percent drug release at 18th hour, time required for 80% drug release and drug entrapment efficiency as dependent variables. FTIR, SEM, sol-gel analysis, equilibrium swelling studies and in-vitro release kinetics were performedfor in-vitro characterization of formulated IPN hydrogels. In-vitro studies carried out at pH 1.2 and pH 7.4 revealed pH independent swelling and drug release from polymeric IPN, providing controlled drug release for an extended period of time with improved entrapment efficiency, thereby concluding that this polymeric blend may be a promising system for the prolonged drug delivery.